Analytic support to intelligence in counterinsurgencies - Perry, Walt L. (RAND Corp., 2008)
Operations in Iraq and Afghanistan have shown that U.S. forces need more-effective techniques and procedures to conduct counterinsurgency. It is likely that U.S. forces will face similar, irregular warfare tactics from future enemies that are unwilling to engage in conventional combat with U.S. forces. This monograph examines the nature of the contemporary insurgent threat and provides insights on using operational analysis techniques to support intelligence operations in counterinsurgencies. The authors examine the stages of an insurgency and discuss the kinds of intelligence that are needed at each stage. A number of techniques--pattern discernment and predictive analysis, for example--appear to show promise of being useful to intelligence analysis. The authors also explore two closely connected methods in depth to examine the interactions between friendly and enemy forces: game theory and change detection.